Various Biomaterials and Techniques for Improving Antibacterial Response - Singh A.; Dubey A.K. (My University, 2025)
The majority of failures in prosthetic implants and devices are caused by infections. Microbial infections are one of the major causes of these failures. The present article reviews various techniques such as modification in surface chemistry/composition and tailored structures (micro to nano) for improving the antibacterial response of prosthetic implants. In addition, the application of external stimulants such as magnetic and electric fields, as well as polarization, is recently realized as a fairly appealing approach to diminish the bacterial population. A comprehensive response of surface modifications as well as external stimuli in inducing the antibacterial response in prosthetic implants has also been summarized. The mechanisms for the antibacterial response due to these modifications, such as generation of toxic metal ions by dissolution of their respective oxides, and production of reactive oxygen species (ROS), such as singlet oxygen, hydroxyl radicals (OH-), hydrogen peroxide (H2O2), superoxides, peroxides (O2-2), etc., have been elaborately discussed. © 2018 American Chemical Society.